Petiveria alliacea extracts uses multiple mechanisms to inhibit growth of human and mouse tumoral cells - Kaur Punit; Arango Amparo; Castañeda Diana; Cifuentes Claudia; Urueña Claudia; Asea Alexzander; Fiorentino Susana (BMC, 2008)
Abstract Background There is ethnopharmacological evidence that Petiveria alliacea can have antitumor activity; however, the mechanism of its cytotoxic activity is not well understood. We assessed multiple in vitro biological activities of an ethyl acetate soluble plant fraction over several tumor cell lines. Methods Tumor cell lines were evaluated using the following tests: trypan blue exclusion test, MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide], flow cytometry, cytoskeleton organization analysis, cell cycle, mitochondria membrane depolarization, clonogenicity test, DNA fragmentation test and differential protein expression by HPLC-Chip/MS analysis. F4 fraction characterization was made by HPLC-MS. Results Petiveria alliacea fraction characterized by de-replication was found to alter actin cytoskeleton organization, induce G2 cell cycle arrest and cause apoptotic cell death in a mitochondria independent way. In addition, we found down regulation of cytoskeleton, chaperone, signal transduction proteins, and proteins involved in metabolic pathways. Finally up regulation of proteins involved in translation and intracellular degradation was also observed. Conclusion The results of this study indicate that Petiveria alliacea exerts multiple biological activities in vitro consistent with cytotoxicity. Further studies in animal models are needed but Petiveria alliacea appears to be a good candidate to be used as an antitumor agent.